2020
DOI: 10.1111/trf.15933
|View full text |Cite
|
Sign up to set email alerts
|

Volume‐dependent effect of stored red blood cells: A secondary analysis of the Age of Blood Evaluation trial

Abstract: Background An increased risk of complications, including death, has been associated with stored red blood cell (RBC) units in observational studies but not in randomized trials. We aimed to evaluate for volume‐dependent effects attributable to length of RBC storage in a secondary analysis of the Age of Blood Evaluation (ABLE) trial. Study Design and Methods In the 2510 critically ill adults from the ABLE trial randomized to receive RBC units stored not more than 7 days or the oldest compatible RBC units, we es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…One theory should be that the patients in the single‐center trauma studies were characterized by overall higher OEIs since they received larger volumes of RCCs in general, and hence a larger accumulated storage lesion. In fact, a sub‐analysis of the ABLE trial, a multicenter study of 2510 critically ill adults, revealed a dose‐dependent relationship between stored RBCs and mortality, with an increased risk of mortality observed in patients transfused stored RBCs after a threshold of six RBC units 32 . In large volume transfused cohorts, the donor variability may be subsumed by the cumulative OEI.…”
Section: Discussionmentioning
confidence: 99%
“…One theory should be that the patients in the single‐center trauma studies were characterized by overall higher OEIs since they received larger volumes of RCCs in general, and hence a larger accumulated storage lesion. In fact, a sub‐analysis of the ABLE trial, a multicenter study of 2510 critically ill adults, revealed a dose‐dependent relationship between stored RBCs and mortality, with an increased risk of mortality observed in patients transfused stored RBCs after a threshold of six RBC units 32 . In large volume transfused cohorts, the donor variability may be subsumed by the cumulative OEI.…”
Section: Discussionmentioning
confidence: 99%
“…In this trial, there was no effect of storage duration on outcomes even in the highest quartile of volume transfused (>30 mL/kg), which equates to approximately 2 to 3 transfusion events per patient over the study period. A dose effect with larger amounts of older red blood cells transfused over short periods of time adversely affecting outcomes is possible and has been reported in retrospective studies and secondary analyses of 2 randomized clinical trials . Third, as a result of using standard delivery of red blood cells, the median storage age was low at 18 days.…”
Section: Discussionmentioning
confidence: 99%
“…Through one or several of these mechanisms, transfusion of older red blood cells may increase the risk of organ failure or death in critically ill patients. Observational studies and exploratory analyses of randomized clinical trials also suggest that for patients who receive larger volumes of older red blood cells, there is an association with poor outcomes …”
Section: Introductionmentioning
confidence: 99%
“…39 Importantly, Markowicz and Engleman showed that dendritic cells are only viable for up to 1 week after blood is donated, which may explain the association between microchimerism and fresh blood transfusion. 20 41 Therefore, if the effect of length of storage time is indeed Ushaped, it is inappropriate to compare the oldest group to the freshest group as the difference between the former and the latter will be smaller. Thus, this may explain why many cohort studies did not report statistically significant differences in the outcome of patients who received very old blood versus those who received fresh blood.…”
Section: Discussionmentioning
confidence: 99%